Study on acoustic source characteristics of gas pipeline leakage. (March 2019) - Baokun, Han; Xiyang, Liu; Bing, Liu; Huaiqian, Bao; Xiangguang, Jiang
The characteristics of acoustic source of gas pipeline leakage determine the accuracy and adaptability of leak detection for gas pipelines based on acoustic method. In order to explore the characteristics of leakage acoustic source of gas pipeline, a physical model of gas pipeline leakage was developed. Initially, generation mechanism of acoustic source of gas pipeline leakage is studied in order to identify the basic principle of leak detection of gas pipeline based on acoustic method. After that, the simulation model is developed according to the basic principle of aeroacoustics, the flow field, and sound source characteristics of the gas pipeline leakage. Then, the experimental platform for the study on acoustic source characteristics of gas pipeline leakage is set up using the basic principle of the leak detection based on acoustic method and simulation results. The characteristics of acoustic source of leakage are obtained through experiments. Finally, the simulation and experimental results of acoustic source of leakage under different operating conditions are compared, and the accuracy of the simulation results is verified, which provides a theoretical basis for the engineering application of leak detection for gas pipeline based on acoustic method. The results show that the acoustic source of gas pipeline leakage is mainly quadrupole source and the leakage acoustic energy is mainly in the range of less than 100 Hz. The mean value of sound pressure level is increased with the pressure in pipeline and the size of leak aperture.